Getting to the Web - Hubbard, Sally (DigItalia, 2007)
This article discusses the long chain of operations involved behind the scenes before, and after, cultural heritage collections make an appearance on the World Wide Web, focusing particularly on Web access and digital preservation. Many institutions are in the process of making the transition from “project-based” to “program-based” digitization, and are attempting to knit together and implement a fully integrated and coherent digitization strategy. Because digital technology has an inherent tendency to break down time-honored barriers and niches, this transition can be difficult. A digitization program is likely to have an impact in many traditional arenas: acquisition; collections conservation and cataloguing; description and access; distribution and exhibition; and intellectual property or digital rights management, in addition to requiring attention to digital capture itself and the management and preservation of digital objects. Digitization programs may therefore require greater consensus and cooperation across an institution, or between institutions, to be successful than was true of limited digital projects undertaken by one department or another. Even after the long upstream journey to a live Web site has been made, the accessibility of collections is a complicated issue with no single solution. A combination of traditional cataloguing; new data standards and protocols; social tagging; full-text availability; thesauri and ontologies; and perhaps eventually some forms of automated visual and or aural indexing may all be required to navigate intelligently through an increasingly massive complex of heterogeneous material.